2015
DOI: 10.3892/ijo.2015.3266
|View full text |Cite
|
Sign up to set email alerts
|

Impaired gap junctions in human hepatocellular carcinoma limit intrinsic oxaliplatin chemosensitivity: A key role of connexin 26

Abstract: Hepatocellular carcinoma (HCC) is generally believed to have low sensitivity to chemotherapeutic agents including oxaliplatin (OXA). Studies have demonstrated that gap junctions (GJs) composed of connexin (Cx) proteins have the potential to modulate drug chemosensitivity in multiple tumor cells. In the present study, we investigated the characteristics of Cx and GJs in HCC at both histologic and cytologic levels, and the effects of GJ and its effective components on OXA cytotoxicity in HCC cells in vitro. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…Our previous study found that compared with normal liver tissue, the expression of Cx32 in HCC tissue is downregulated, and the positively expressed protein shows significant ectopic expression from the cell membrane to the cytoplasm (18). We further analyzed its relationship to clinicopathological characteristics and found that the expression of Cx32 was not correlated with age, sex, tumor size, TNM stage, background of liver disease, or vascular embolus (all P>0.05), but negatively correlated with histological grade and lymph node metastasis (all P<0.05) (Table III).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study found that compared with normal liver tissue, the expression of Cx32 in HCC tissue is downregulated, and the positively expressed protein shows significant ectopic expression from the cell membrane to the cytoplasm (18). We further analyzed its relationship to clinicopathological characteristics and found that the expression of Cx32 was not correlated with age, sex, tumor size, TNM stage, background of liver disease, or vascular embolus (all P>0.05), but negatively correlated with histological grade and lymph node metastasis (all P<0.05) (Table III).…”
Section: Resultsmentioning
confidence: 99%
“…Archival normal liver (20 cases) and HCC (76 cases) paraffin blocks were collected as described in an earlier study (18) to determine the relationship of Cx32 expression to clinicopathological parameters. Another set of 34 cases of archival paraffin-embedded formalin-fixed HCC tissues were also collected at our institution from January 2014 to June 2015 to define the correlation between Cx32 and other indicators.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, numerous studies have indicated that Cx contributes to chemoresistance in several types of tumour. Upregulated Cx26 contributed to gefitinib resistance in non-small cell lung cancer cells (10), while increased Cx26 expression was able to reverse oxaliplatin resistance in hepatocellular carcinoma (11). Upregulation of Cx43 led to the insensitivity…”
Section: Introductionmentioning
confidence: 99%